Clinical Decision-Making Regarding the Added Value of Postoperative Chemotherapy After Complete Secondary Cytoreductive Surgery in Unifocal First Recurrent Epithelial Ovarian Cancer—An International Expert Survey - Renée E. W. M. van de Vorst; Sophie S. M. Pelk; Eelke H. Gort; Petronella O. Witteveen; Ronald P. Zweemer; Cornelis G. Gerestein (Journal of Personalized Medicine, 2026)
Background: Secondary cytoreductive surgery (SCS) followed by postoperative chemotherapy is a recognized option for select patients with platinum-sensitive first recurrent epithelial ovarian cancer (EOC), supported by the DESKTOP-III and SOC-1 trials. Neither trial reported chemotherapy rates stratified by lesion number or resection status. As a result, the added value of postoperative chemotherapy after complete resection of a unifocal recurrence remains unclear. This study aimed to evaluate current clinical practice and factors influencing this decision. Methods: A cross-sectional survey was conducted among gynecological and medical oncologists from international expert oncological centers, assessing definitions of unifocal recurrence, current postoperative chemotherapy practice after complete SCS, perceived clinical value and strength of the supporting evidence, and factors influencing decision-making. Results: Twenty of 48 invited experts responded (41.7%). Respondents applied different definitions of unifocal recurrence, leading to variable estimates of the annual number of patients undergoing SCS. Respondents perceived postoperative chemotherapy to have meaningful clinical value, despite rating the supporting evidence as weak. A proportion did not routinely administer postoperative chemotherapy after complete SCS, managing patients with observation alone. Decisions to omit chemotherapy were influenced by institutional, clinical, and patient-related factors. Overall, 82% of respondents considered a randomized trial comparing chemotherapy with observation clinically valuable. Conclusions: Clinical practice regarding postoperative chemotherapy after complete SCS for a first unifocal recurrence of EOC varies among international expert oncological centers. The absence of a uniform definition of unifocal recurrence and lack of direct evidence regarding postoperative chemotherapy omission highlight the need for standardized definitions and prospective randomized evaluation of chemotherapy versus observation.